2022
DOI: 10.7150/thno.71400
|View full text |Cite
|
Sign up to set email alerts
|

Loss of MLKL ameliorates liver fibrosis by inhibiting hepatocyte necroptosis and hepatic stellate cell activation

Abstract: Background: Liver fibrosis affects millions of people worldwide without an effective treatment. Although multiple cell types in the liver contribute to the fibrogenic process, hepatocyte death is considered to be the trigger. Multiple forms of cell death, including necrosis, apoptosis, and necroptosis, have been reported to co-exist in liver diseases. Mixed lineage kinase domain-like protein ( MLKL ) is the terminal effector in necroptosis pathway. Although necroptosis has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 67 publications
0
25
0
Order By: Relevance
“…Besides macrophages, necroptosis also occurs in other kinds of liver cells during liver fibrogenesis. For example, recent research has proved that Mlkl knockout significantly alleviates BDL-induced mouse liver fibrosis by reducing hepatocyte necroptosis and hepatic stellate cell activation [ 36 ]. All these results indicate that necroptosis is a vital player of cholestatic liver injury/fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Besides macrophages, necroptosis also occurs in other kinds of liver cells during liver fibrogenesis. For example, recent research has proved that Mlkl knockout significantly alleviates BDL-induced mouse liver fibrosis by reducing hepatocyte necroptosis and hepatic stellate cell activation [ 36 ]. All these results indicate that necroptosis is a vital player of cholestatic liver injury/fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Necroptosis and MLKL expression are associated with NAFLD development. Previous studies using MLKL knockout mice have shown that MLKL inhibition decreases hepatic inflammation, steatosis, and fibrosis. , In this study, the MLKL inhibitor directly reduced fibrosis in HSCs, suggestive of a mechanism inhibiting NAFLD development via inhibition of immune cell and HSC activities.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that NSA and TC13172, well-known inhibitors of MLKL, target N-terminal domains to suppress MLKL oligomerization. 18,19 Because MLKL plays a crucial role in necroptosis and necrosis, MLKL inhibitors may alleviate inflammation and liver fibrosis in NAFLD. However, the anti-inflammatory and antifibrotic effects of MLKL inhibitors have not yet been thoroughly evaluated.…”
mentioning
confidence: 99%
“…Liver fibrosis is revealed to be the outcome of multiple processes, such as the production of reactive oxygen species, the release of inflammatory factors, the activation of HSCs, the excessive accumulation of ECM, and angiogenesis. [25] Peptides with the ability to relieve or reverse these processes have been explored as antifibrotic peptides for the treatment of liver fibrosis. Oxidative stress is a key factor that can trigger morphological change and activation of HSCs in the development of liver fibrosis.…”
Section: Antifibrotic Peptides For the Treatment Of Liver Fibrosismentioning
confidence: 99%